Tactics of the Human Experimental Technics in American Fiction - Shackelford, Laura; Project Muse. (University of Michigan Press, 2014)
"Tactics of the Human: Experimental Technics in American Fiction examines the ways contemporary American fiction develops digital cultures through the creative transposition of digital rhetorics and technological practices, incorporating devices such as the hyperlink, network, and recursive processing into print or in translating a classic print narrative into a digital hypertext fiction. These literary experiments with early digital cultures from the 1990s comparatively retrace and speculate on the digital's transformative influence on prior understandings of the human, of social lives, and of individuals' relations to material lifeworlds, exploring the consequences of the apparent plasticity of the boundaries of the human, particularly for women, subaltern subjects, and others already considered liminally human. As these texts query the digital technics entering into textual practices, subjectivity, spatial practices and social networks, lived space, nation, and economic circulation, they reconceive their own literary print narrative methods and material modes of circulation in order to elaborate on unnoticed potentialities and limits of digital technics, providing a crucial means to reorient digital cultures of the present"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: SOCIAL SCIENCE / Media Studies; LITERARY CRITICISM / American / General; Experimental fiction, American -- History and criticism; Literature and the Internet -- United States; Hypertext fiction -- History and criticism; Human body and technology in literature; Literature and technology -- United States; American fiction -- History and criticism; Electronic books